Muscle biopsy in Pompe disease Biópsia muscular na doença de Pompe - Lineu Cesar Werneck; Paulo José Lorenzoni; Cláudia Suemi Kamoi Kay; Rosana Herminia Scola (Arquivos de Neuro-Psiquiatria)
Pompe disease (PD) can be diagnosed by measuring alpha-glucosidase levels or by identifying mutations in the gene enzyme. Muscle biopsies can aid diagnosis in doubtful cases. Methods: A review of muscle biopsy from 19 cases of PD (infantile, 6 cases; childhood, 4 cases; and juvenile/adult, 9 cases). Results: Vacuoles with or without glycogen storage were found in 18 cases. All cases had increased acid phosphatase activity. The vacuole frequency varied (almost all fibers in the infantile form to only a few in the juvenile/adult form). Atrophy of type 1 and 2 fibers was frequent in all forms. Atrophic angular fibers in the NADH-tetrazolium reductase and nonspecific esterase activity were observed in 4/9 of the juvenile/adult cases. Conclusion: Increased acid phosphatase activity and vacuoles were the primary findings. Most vacuoles were filled with glycogen, and the adult form of the disease had fewer fibers with vacuoles than the infantile or childhood forms. O diagnóstico da doença de Pompe (PD) pode ser feito pela dosagem da enzima alfa-glicosidase ou pela mutação do seu gene codificador. A biópsia muscular pode ajudar em casos duvidosos. Métodos: Revisão das biópsias musculares de 19 casos de PD (forma infantil, 6 casos; infantil tardia, 4; e juvenil/adulto, 9). Resultados: Encontrados vacúolos em 18 casos, com ou sem depósito de glicogênio. Todos mostraram aumento da fosfatase ácida. Os vacúolos estavam presentes na maioria das fibras nas formas infantis, menos frequentes nas formas juvenil e mais raros nas formas do adulto. A atrofia de fibras dos tipos 1 e 2 ocorreram em todas as formas. Fibras atróficas na NADH-tetrazolium redutase e esterase não específica foram observadas em 4/9 das formas infantil tardia/adulta. Conclusões: Os dados mais frequentes foram vacúolos, preenchidos por glicogênio com atividade aumentada da fosfatase ácida. A forma adulta apresenta menor número de vacúolos que as formas infantil e infantil tardia.